Percolation of topologically equivalent quadrilateral systems - Hernal, Mary Joyce O.
Percolation thresholds in quasi-one dimensional systems were compared with those of the two dimensional systems. Specifically, the equivalence of spanning the space in square lattice with square (clumped) banned sites to that of a homogeneous rectangular lattice of the same number of accessible site is demonstrated using the idea of site percolation. To measure the percolation thresholds in rectangular lattices, spanning is defined horizontally; while instead of using the traditional one-way or two-way spanning for a constrained two dimensional system, a method in looking for a cluster that surrounds the square banned sites is employed. Fifty percolating samples were considered in each process.